Perbedaan Prestasi Siswa Model Pembelajaran Kooperatif Tipe STAD dan NHT Materi Koordinat Kartesius - Rahman Hidayat; Sripatmi Sripatmi; Muhammad Turmuzi; Nani Kurniati (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to determine whether there are differences in maths learning achievement between classes taught by cooperative learning model Student Team Achievement Division (STAD) type and class taught by cooperative learning type Numbered Head Together (NHT) in material sistim coordinat cartesius class VIII SMP Negeri 1 Kediri 2018/2019 school year. Data collection techniques in this study are test techniques with instruments in the form of learning achievement test, learning implementation observasion sheets and learning implementation. Data analysis techniques use descriptive statistics. Hypothesis test of students' final ability (posstest) with t-test of two parties at a significance level of 5% resulted in tcount <ttable namely 0,020 < 2.030 which means that there were nothing differences in mathematics learning achievement between classes taught by cooperative learning model Student Team Achievement Division ( STAD) and classes taught by the cooperative learning model Numbered Head Together (NHT) in material sistim coordinat cartesius class VIII SMP Negeri 1 Kediri academic year 2018/2019.